Mental health treatment and access for emerging adults in Canada: a systematic review - Murray, Jonah Kynan; Knudson, Sarah (Frontiers in Public Health, 2023)
Introduction Research into the mental healthcare of emerging adults (18–25) in Canada has been limited, despite this developmental period being widely considered a vulnerable time of life. As such, we aimed to identify the greatest barriers emerging adults faced in accessing mental healthcare in Canada, particularly in relation to the Canadian healthcare system which operates on a universal funding model but is challenged by funding shortfalls and a complex relationship to the provinces. Methods We systematically examined 28 pieces of literature, including academic and technical literature and publications from government organizations, focused on emerging adults and the Canadian mental healthcare system. Results Findings demonstrated that stigma, a lack of mental health knowledge, cost, and interpersonal factors (e.g., one’s parental, peer, and romantic supports demonstrating negative views toward mental healthcare may deter treatment; emerging adults demonstrating concerns that accessing mental healthcare may lead to peer rejection) acted as barriers to help-seeking in emerging adults. Additionally, a lack of national institutional cohesion and a lack of policy pertaining to emerging adult healthcare acted as barriers to adequate mental healthcare in this demographic. Discussion Improving mental health education early in life shows promise at reducing many of the barriers emerging adults face in accessing mental healthcare. Further, policies directed at ensuring a cohesive national mental health system, as well as policies directly designed to care for emerging adult mental health needs, could act as the next steps toward ensuring an accessible and effective Canadian mental healthcare system that can serve as a model for other nations.